2021
DOI: 10.1126/sciadv.abf7820
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered cell membrane–coated nanoparticles for targeted delivery of dexamethasone to inflamed lungs

Abstract: As numerous diseases are associated with increased local inflammation, directing drugs to the inflamed sites can be a powerful therapeutic strategy. One of the common characteristics of inflamed endothelial cells is the up-regulation of vascular cell adhesion molecule–1 (VCAM-1). Here, the specific affinity between very late antigen–4 (VLA-4) and VCAM-1 is exploited to produce a biomimetic nanoparticle formulation capable of targeting inflammation. The plasma membrane from cells genetically modified to constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 53 publications
3
108
0
Order By: Relevance
“…Alternatively, targeted EC therapies, as discussed below, may be considered for the resolution of vascular inflammation at the site of the activated endothelium in atherosclerosis. Prospective agents for targeted resolution include ICAM-1- or VCAM-1-targeted nanocarriers, which have previously been employed to limit neurovascular ( Lutton et al, 2017 ; Marcos-Contreras et al, 2020 ) and pulmonary inflammation ( Li S. et al, 2018 ; Park et al, 2021 ) in experimental models of disease.…”
Section: The Vascular Endothelium As An Emerging Therapeutic Target For Atherosclerosismentioning
confidence: 99%
“…Alternatively, targeted EC therapies, as discussed below, may be considered for the resolution of vascular inflammation at the site of the activated endothelium in atherosclerosis. Prospective agents for targeted resolution include ICAM-1- or VCAM-1-targeted nanocarriers, which have previously been employed to limit neurovascular ( Lutton et al, 2017 ; Marcos-Contreras et al, 2020 ) and pulmonary inflammation ( Li S. et al, 2018 ; Park et al, 2021 ) in experimental models of disease.…”
Section: The Vascular Endothelium As An Emerging Therapeutic Target For Atherosclerosismentioning
confidence: 99%
“…Recently, it has been reported that the NSC can be better used to promote damage repair by engulfing anti-inflammatory nanoparticles (104). Exploring the effect of exogenous NSC on SCI, the way of combining new materials and targeted delivery of NSC may become a research hotspot in the future (105).…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…(B) Schematic illustration of genetically engineered cell membrane–coated nanoparticles for targeted DEX to inflamed lungs. (Reproduced with permission from Park et al (2021) ).…”
Section: Engineered Cell Membrane-encapsulated Nanoparticlesmentioning
confidence: 99%